Examining the relationship between anhedonia symptoms and trait positive appraisal style in adolescents: A longitudinal survey study. (31st July 2021) - Yilmaz, Merve; Psychogiou, Lamprini; Ford, Tamsin; Dunn, Barnaby D.
ABSTRACT: Introduction: Anhedonia, defined as a loss of interest and pleasure in previously enjoyable activities, is a core symptom of depression that predicts a poor treatment response in adolescents. We know little about the cognitive vulnerability factors that contribute to the development of anhedonia in youth. This cross‐sectional and longitudinal survey study investigated the link between anhedonia symptoms and cognitive appraisal of positive affect. Methods: Baseline data were collected from 392 secondary school students in the UK (aged 13–16, 54 % Female), 170 of whom went on to complete the three‐month follow‐up assessment (a 43 % response rate). Participants rated their anhedonia symptoms and appraisal styles which were measured in terms of use of amplifying appraisals, dampening appraisals, and fear of positive emotion. Results: At baseline, greater anhedonia was significantly associated with increased levels of dampening and reduced levels of amplifying but was not significantly related to fear of positive emotion. Prospectively, greater baseline levels of amplifying uniquely predicted lower anhedonia severity at three‐month follow‐up, and vice‐versa. There was no evidence for reciprocal prospective associations between anhedonia and, appraisal styles of dampening and fear of positive emotion. Conclusion: These results indicate that cognitive appraisal of positive affect is associated with concurrent and to some extent can predict future symptoms of anhedonia in youth.